2012
DOI: 10.1029/2012gl051015
|View full text |Cite
|
Sign up to set email alerts
|

Remote triggered seismicity caused by the 2011, M9.0 Tohoku‐Oki, Japan earthquake

Abstract: Seismic waves from large earthquakes have been shown to trigger seismicity large distances from a mainshock, and this is termed remotely or dynamically triggered seismicity. We performed a global search for seismicity potentially triggered by the seismic waves from the 2011, M9.0, Tohoku‐Oki, Japan Earthquake. Using seismograms from global seismic networks and an event catalog, we search for earthquakes and tremors instantaneously triggered during the passing of the seismic waves, as well as for statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 26 publications
2
65
0
Order By: Relevance
“…The 2010 Maule, Chile and 2011 Tohoku, Japan great earthquakes struck along coastlines where extensive GPS networks had accumulated up to two decades of preceding ground motions that could be modeled by slip-deficit distributions on the megathrust (e.g., Nishimura et al, 2004;Suwa et al, 2006;Hashimoto et al, 2009;Loveless and Meade, 2010;. While these measurements have limited sensitivity to coupling far offshore, and the slip-deficit models failed to anticipate the location of largest slip for the 2011 event, these studies demonstrated the potential for mapping out future large earthquake rupture zones.…”
Section: Great Earthquake Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2010 Maule, Chile and 2011 Tohoku, Japan great earthquakes struck along coastlines where extensive GPS networks had accumulated up to two decades of preceding ground motions that could be modeled by slip-deficit distributions on the megathrust (e.g., Nishimura et al, 2004;Suwa et al, 2006;Hashimoto et al, 2009;Loveless and Meade, 2010;. While these measurements have limited sensitivity to coupling far offshore, and the slip-deficit models failed to anticipate the location of largest slip for the 2011 event, these studies demonstrated the potential for mapping out future large earthquake rupture zones.…”
Section: Great Earthquake Quantificationmentioning
confidence: 99%
“…At the same time, there is quite compelling evidence for recent great earthquakes producing dynamic triggering of small events on a global scale during passage of surface waves (e.g., West et al, 2005;Velasco et al, 2008;Parsons and Velasco, 2011;Gonzalez-Huizar et al, 2012), as well as somewhat more ambiguous delayed intervals of rate increases (Pollitz et al, 2012;Gonzalez-Huizar et al, 2012). Attempts to detect physical connections between delayed remote events in the form of dynamicallytriggered seismicity rate increases at sites of future great events coincident with passage of seismic waves from earlier great events have not established statistically robust interactions (e.g., van der Elst et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical responses of the earth to the great earthquakes were investigated to understand the influence of the great earthquakes (West et al, 2005;Lei et al, 2011;Miyazawa, 2011;Gonzalez-Huizar et al, 2012;Lee and Hong, 2014). Dynamic triggering of microearthquakes was widely observed in active tectonic regions up to tens of thousands of kilometers (Hill et al, 1993;West et al, 2005;Durand et al, 2010;Peng and Gomberg, 2010;Lei et al, 2011;Miyazawa, 2011;Shelly et al, 2011;Wu et al, 2011;Gonzalez-Huizar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These include instantaneous triggering of microearthquakes (e.g., Velasco et al, 2008;Jiang et al, 2010), deep tectonic tremor (e.g., Peng and Gomberg, 2010), earthquake swarms (Gonzalez-Huizar et al, 2012), slow-slip events (Hirose et al, 2012;Zigone et al, 2012), and near-surface icequakes (Peng et al, 2014). Among these seismic/aseismic responses, tremor has been observed in a number of plate-bounding tectonic environments around the Pacific Rim (Peng and Gomberg, 2010;Beroza and Ide, 2011;and references therein).…”
Section: Introductionmentioning
confidence: 99%